Microbiological aspects of Escherichia coli in urinary tract infections in sows of commercial farms in Sinop-MT - Venancio, L. F. B.; Ducatti, K. R.; Lima, M. O.; Vieira, T. B. (Scientific Electronic Archives, 2017)
Urinary infections (UI) in nuts are highly prevalent in modern intensive farming systems and cause significant economic losses, especially for reproductive failure and shortening the life of the array. The most frequently isolated agent is the bacterium Escherichia coli (E. coli). Variables such as environmental contamination pressure, management, nutrition, physiological and anatomical facilities and conditions of the animal itself are directly linked to illness. The objective of this work was to monitor microbiological urine nuts with suspected UI on commercial farms in the municipality of Sinop-MT, by counting of aerobic mesophilic total of Escherichia coli research and antimicrobial susceptibility profile. Urine samples with aerobic mesophilic total counts above 105UFC / mL were considered positive, confirming IU in 12 samples (28.57%) of the 42 females subjected to collections. Of the 42 urine samples, 305 were isolated colonies of Gram negative bacteria and through biochemical tests it was confirmed E.coli in 165 (54.09%) of these. In 37 (88.09%) of the 42 samples collected had involvement of E. coli, with or without other pathogens and all positive samples for UI by total aerobic mesophilic bacteria count showed. Through the antimicrobial susceptibility profile test, E. coli strains showed sensitivity to the following percentages: Gentamicin (100%), Streptomycin (98.70%), Neomycin (92.85%) Doxycycline (91.55%) , Enrofloxacin (80.51%), Sulfazotrim (64.28%), Ampicillin (62.97%), tetracycline (61.68%) and Amoxicillin (24.04%). The diagnosis of UI should be carried out thoroughly, assessing clinical and microbiological aspects, for the identification of the microorganism involved and the realization of antimicrobial susceptibility testing prevents the appearance of multi-resistant bacterial strains.